2018
DOI: 10.1016/j.mce.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of mRNA expression and alternative splicing during mouse sex determination

Abstract: Mammalian sex determination hinges on sexually dimorphic transcriptional programs in developing fetal gonads. A comprehensive view of these programs is crucial for understanding the normal development of fetal testes and ovaries and the etiology of human disorders of sex development (DSDs), many of which remain unexplained. Using strand-specific RNA-sequencing, we characterized the mouse fetal gonadal transcriptome from 10.5 to 13.5 days post coitum, a key time window in sex determination and gonad development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 111 publications
7
64
2
Order By: Relevance
“…Here, we analyze the developing mouse ovary using scRNAseq at seven time points between E11.5 and postembryonic day 5 (P5), involving a total of 52,542 cells. During E12.5 to P5, female germ cells express several thousand genes differentially as they pass through six meiotic stages, extending previous studies ( 37 , 42 , 44 , 45 ). We also define genes expressed by epithelial progenitors and clarify the similar but distinct genetic programs of BPG and EPG cell progenitors ( 8 , 21 23 ).…”
supporting
confidence: 83%
“…Here, we analyze the developing mouse ovary using scRNAseq at seven time points between E11.5 and postembryonic day 5 (P5), involving a total of 52,542 cells. During E12.5 to P5, female germ cells express several thousand genes differentially as they pass through six meiotic stages, extending previous studies ( 37 , 42 , 44 , 45 ). We also define genes expressed by epithelial progenitors and clarify the similar but distinct genetic programs of BPG and EPG cell progenitors ( 8 , 21 23 ).…”
supporting
confidence: 83%
“…To characterize cell identity during differentiation of human iPSCs to gonadal cells, we devised a panel of marker genes for gonad development ( Figure 1 and Table S1 ). Publicly available RNA-sequencing (RNA-seq) data from mouse, including bulk RNA-seq from embryonic day (E) 10.5–E13.5 gonads ( Zhao et al., 2018 ) and single-cell RNA-seq (scRNA-seq) of sorted gonadal cells ( Stévant et al., 2019 ), were interrogated to confirm marker expression. The Lhx9 , Nr5A1 , Gadd45g , Wt1 , Gata4 , Fog2/Zfpm2 , Nr0B1 , Emx2 , and Hsd3b2 genes were chosen to represent the bipotential gonad.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past two decades, intensive efforts have been made to investigate the genetic network at play during sex determination and gonadal cell differentiation, using large-scale transcriptomic methods, such as microarrays, on whole gonads or sorted cells (Beverdam and Koopman, 2006;Bouma et al, 2007Bouma et al, , 2010Jameson et al, 2012;Munger et al, 2013;Nef et al, 2005;Small et al, 2005). More recently, RNA sequencing (RNA-seq) and single-cell RNA sequencing (scRNA-seq) have been used (Inoue et al, 2016;McClelland et al, 2015;Sté vant et al, 2018;Zhao et al, 2018). These studies revealed the bipotential state of the XX and XY gonads before sex determination and highlighted the gene expression dynamics and mutually antagonistic genetic programs controlling the establishment of sexual identity in the supporting cell lineage.…”
Section: Introductionmentioning
confidence: 99%